The phantom of the opera - Schumacher, Joel, 1939-; Butler, Gerard, 1969-; Rossum, Emmy, 1986-; Wilson, Patrick, 1973-; Richardson, Miranda; Driver, Minnie; Mathieson, John, 1961-; Lloyd Webber, Andrew, 1948-; Leroux, Gaston, 1868-1927.; Warner Bros. Pictures (1969- ); Odyssey Entertainment (Firm); Really Useful Films; et al. ([Burbank, CA] : Warner Bros. Pictures, 2005)
Tells the story of a disfigured musical genius who haunts the catacombs beneath the Paris Opera, waging a reign of terror over its occupants. When he falls fatally in love with Christine, the Phantom devotes himself to creating a new star for the Opera, exerting a strange sense of control over the young soprano as he nurtures her extraordinary talents.
Based on the novel "Le Fantome de l'Opera by Gaston Leroux and the stage musical by Andrew Lloyd Webber.
Videodisc release of the 2004 motion picture.
Special features include: scene selection, theatrical trailer.
Director of photography, John Mathieson ; art directors, John Fenner, Paul Kirby ; editor, Terry Rawlings ; original music, Andrew Lloyd Webber ; costume designer, Alexandra Byrne ; production designer, Anthony Pratt ; visual effects supervisor, Nathan McGuinness ; special effects supervisor, Peter Hutchinson.
Gerald Butler, Emmy Rossum, Patrick Wilson, Miranda Richardson, Simon Callow, Ciaran Hinds, Jennifer Ellison, James Fleet, Victor McGuire, Kevin R. McNally, Murray Melvin, Minnie Driver.
DVD; Dolby Digital 5.1 surround.
Keywords: Opera de Paris -- Drama; Phantom of the Opera (Fictitious character) -- Drama; Sopranos (Singers) -- Drama; Feature films; Musical films; Paris (France) -- Drama